PELAKSANAAN PEWARISAN HARTA PUSAKA TINGGI MINANGKABAU DI NAGARI KOTO NAN GADANG KOTA PAYAKUMBUH DIHUBUNGKAN DENGAN FALSAFAH ADAT BASANDI SYARA’ SYARA’ BASANDI KITABULLAH - Hannana Fitria (Law Department Jenderal Achmad Yani University, 2025)
Minangkabau is an area in Indonesia where the community can be found regulated based on the mother law or the matrilineal system starting from a small living environment (family) to the highest living environment, namely a nagari. Minangkabau inheritance law is a concrete issue that is still constantly being questioned because on the one hand Minangkabau inheritance law is a continuation in accordance with the order of the arrangement according to the matrilineal law, but on the other hand it is related and influenced by sharia law (religion). The indigenous people of Minangkabau generally adhere to Islam and have hereditary guidelines and provisions that the status of Minangkabau people will be revoked if they are not Muslims. The Minangkabau philosophy which is the fundamental teaching is